LOWER TRIASSIC (INDUAN TO OLENEKIAN) CONODONTS, FORAMINIFERA AND BIVALVES FROM THE AL MAMALIH AREA, DEAD SEA, JORDAN: CONSTRAINTS ON THE P-T BOUNDARY (Rivista italiana di Paleontologia e Stratigrafia, 2018)
Upper Permian to Lower Triassic successions exposed in the Al Mamalih area, east of the Dead Sea, Jordan record the transition between the alluvial Umm Irna Formation (Upper Permian) and the overlying shallow marine Ma’in Formation (Lower Triassic). The Permian-Triassic boundary is constrained either within a hiatus represented by a sequence boundary between these formations or within ca 15 m of shallow marine beds overlying the boundary. Above the sequence boundary reddened, shallow-marine beds (Himara Member) mark the initial Triassic (presumed early Induan) marine transgression (Himara Member). Absence of both body fossils and vertical infaunal burrows indicates low-diversity, ecosystems following the Permian-Triassic extinction event. A gradational upward increase in grey, green and yellow siltstones beds (Nimra Member), accompanied by a concomitant increase in bioturbation (surface traces and infaunal vertical burrows), bivalves and brachiopods, stromatolites, conchostracans and lingulids in the lower part of the Nimra Member indicates colonisation of the substrate under shallow marine conditions during the recovery phase. Shallow-water carbonates in the Nimra Member yielded an abundant, low diversity assemblage of conodonts (e.g. Hd. aequabilis and H. agordina) and a foraminifera assemblage (Postcladella gr. kalhori-Earlandia spp.-Ammodiscus jordanensis n. sp.) that are interpreted as euryhaline recovery taxa that characterise the the mid-late Induan. Abundant new material has allowed revision of the conodont apparatus and the foraminifera include a new species Ammodiscus jordanensis n. sp. of Induan age. The discovery of the bivalves Claraia bittneri (C. aurita group) and Eumorphotis multiformis is worthy to note. Upper Permian alluvial lithofacies (Jordan) pass basinwards, about 50 km to the northwest, to coeval shallow marine siliciclastic and carbonates in the Negev and Mediterranean coast of Israel.